DETERMINAN KINERJA KEUANGAN PEMERINTAH DAERAH (Studi Kasus Pada Pemda Se Jawa Timur Tahun 2020-2022) (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2024)
Â ABSTRACT Financial performance assessments are used to measure plan achievement, both on an individual and organizational scale. This allows determining whether decision making was carried out fairly and rationally. Budgets are important tools for determining, allocating, and stabilizing government resources, planning, monitoring operations, and assessing organizational performance. In this research, quantitative descriptions are used. Through analysis, this research looks at how all independent variables have an impact on the dependent variable. Secondary data created by other parties is used as a data source. East Java regional government website,www.djpk.depkeu.go.id , provides secondary data for the 2020â€“2022 APBD realization report containing data on the capital expenditure budget and PAD. The results of the research show that the financial performance of regional governments simultaneously affects capital expenditure and local original income; However, capital expenditure does not affect regional government financial performance, and local revenue greatly influences regional government financial performance. Keywords: Financial Performance, Capital Expenditure, Local Revenue